ANALISIS PEMBERIAN REWARD PADA SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN DI PT. SWAMEDIA INFORMATIKA - Andriana, Anna Dara; Susanto, Rani (Majalah Ilmiah UNIKOM, 2020)
The Purpose of Human Resource Management Information System is to ensure that companies can achieve strategic objectives with all as human resources that can be relied upon to meet the needs of companies with good quality. The Human Resources Management Information System consists of several modules that are interrelated to produce information to support the results of human resource management in the company. Rewards to Employees is one of the modules of the Human Resources Management Information System that is important because rewards are a form of appreciation from the company to employees with the hope as motivation for employees to excel in achieving company goals. The problem that occurs in this company is when determining which employees are entitled to receive rewards. The current assessment still does not pay attention to the level of importance in each of the assessment criteria so that frequent valuation errors and rewards are given to employees. Therefore, giving rewards to employees must be done well and can be accounted for. Analytical Hierarchy Process method or called AHP is used to assist in the determination of employees who are entitled to receive rewards. AHP method is a method for solving a complex situation that is not structured into a component and hierarchy arrangement by providing subjective values and determining which variable has the highest priority. This method can provide recommendations for rewarding employees based on the highest value as the best value. Key words: Human Resource Management Information System, Analytical Hierarchy Process, Reward